Commercialization of Bambara Nut Production in Nigeria - Abraham FALOLA; Ridwan MUKAILA; Abel Ojochegbe AHMED (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
The global population increases daily, which requires a considerable increase in food production. Bambara nut is an important staple food crop capable of supplying essential nutrients to the body and providing the farmers with income, yet it is underutilized. This study, therefore, assessed the commercialization of Bambara nut production in Nigeria to enhance food availability. Primary data were gathered from 240 respondents and analysed using descriptive statistics, household commercialization index (HCI), and the Tobit model. The results revealed that the mean HCI was 56%, indicating that there exists a gap of 44% for Bambara nut farmers to reach full commercialization. Access to credit, household size, age, farming experience, the quantity of fertilizer, farm output, and distance to the market were significant factors influencing the degree of Bambara nut commercialization. Inadequate access to credit/loan facilities, long-distance to market, high cost of inputs, poor road network to transport produce, and incidence of pests and diseases were the militating constraints to commercialization of Bambara nut production. This study advocates for the provision of credit and inputs, by government and financial institutions, to the farmers to improve their production and commercialization endeavours.